2008
DOI: 10.1108/02635570810904613
|View full text |Cite
|
Sign up to set email alerts
|

Financial early‐warning models on cross‐holding groups

Abstract: Purpose -This paper primarily uses statistical methods to establish financial early-warning models that make it possible to predict, in advance, the probability of a company experiencing financial distress. Design/methodology/approach -In its empirical analysis, this is the first study that attempts to use financial ratios and non-financial ratios as variables to analyze business groups, and the present study uses the (K-S tests), and (M-U tests) and logit regressions model. Findings -Financial ratio variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It is the ratio of net income to average net equity (Geng et al , 2015; Huang et al , 2017). Higher the ROE for the company, the more income for shareholders, as it reflects the bottom-line measure of performance (Lieu et al , 2008; Ross et al , 2013). It is one of the vital predictors for measuring financial distress and has a negative role in predicting corporate failure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the ratio of net income to average net equity (Geng et al , 2015; Huang et al , 2017). Higher the ROE for the company, the more income for shareholders, as it reflects the bottom-line measure of performance (Lieu et al , 2008; Ross et al , 2013). It is one of the vital predictors for measuring financial distress and has a negative role in predicting corporate failure.…”
Section: Methodsmentioning
confidence: 99%
“…Net profit margin (NPM) is defined as the ratio of net profit after tax to net sales. The higher the NPM, the better it is for the firm (Lieu et al , 2008). Udin et al (2017) found NPM to be negatively associated with the probability of financial distress, which suggests that decreasing profit margin for the firm leads to increased chances of corporate failure.…”
Section: Methodsmentioning
confidence: 99%
“…In the framework of seeking to build such an early warning system for financial distress, recent studies related to financial distress also suggest that CG mechanisms and IC could have a significant impact on the likelihood of a firm's financial distress (Cardoso et al , 2019; Udin et al , 2017; Shahwan, 2015; Elloumi and Gueyie, 2001; Demirkan and Platt, 2009; Li et al , 2008; Lieu et al , 2008; Parker et al , 2002). For instance, Cardoso et al (2019) support the existence of a significant U-shaped format between the board size and the likelihood of firm financial distress.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, the association between managerial ownership and the probability of financial distress is insignificant. Lieu et al (2008) argue that financial distress is less likely to have occurred when a firm increasingly depends on independent directors and supervisors.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to Lieu et al (2008), the consideration over time span prior to distress is important upon examining the predictor variables for corporate financial distress. The study found that financial ratios were the main predictors at one and two years prior to distress, while at three years prior to distress there were one financial ratio and two ownership structure variables that showed significant explanatory power.…”
Section: Resultsmentioning
confidence: 99%